2019
DOI: 10.1108/f-01-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Implementing sustainable facility management

Abstract: Purpose The development of sustainable facilities management (FM) practices requires active and integrated engagement of the FM organization. Building on a three-year research project (2015-2018) within Nordic Built that aims to strengthen FM competencies in the Scandinavian countries, this paper aims to list and document the challenges and barriers of implementing sustainability as identified by the Scandinavian FM practitioners who took part in this research. Design/methodology/approach The paper builds on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 35 publications
3
40
0
1
Order By: Relevance
“…Støre-Valen and Buser (2019) focused on how FM practices can improve sustainability efforts. Therefore, their work relates to the management stream.…”
Section: Resultsmentioning
confidence: 99%
“…Støre-Valen and Buser (2019) focused on how FM practices can improve sustainability efforts. Therefore, their work relates to the management stream.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the results of this paper can assist FM managers in a) identifying and measuring sustainability performance, b) integrating stakeholders and users in the goalsetting process, and c) clearly communicating sustainability goals. This responds directly to the critical challenge businesses face in addressing sustainability, as Nielsen et al [10] and Støre-Valen and Buser [13] identified, in the FM discipline.…”
Section: Discussionmentioning
confidence: 98%
“…Based on stakeholder theory, organizations define key stakeholders, assess their impact on them, and incorporate their needs into the value-creation process. For instance, in FM, stakeholder involvement is perceived as a remedy to overcoming barriers to implementing sustainability practices [13]. Similarly, organizations must consider the environment and society as their key stakeholders to achieve long-term sustainability.…”
Section: Stakeholder Theorymentioning
confidence: 99%
“…By examining the relationships between the use of facility services and their impact on educational achievement, a facility services typology is tried to establish the effects of services used on stability levels and learning outcomes about the costs and risks of their processes. Store-Valen and Buser (2018) and Alfalah and Zayed (2020) stated that FM has a key role in implementing sustainability goals and emphasized that FM education and curriculums must be developed to achieve these goals. Similarly, Jensen et al (2014) reveal competencies and new knowledge in urban FM, ranked highest in Finland.…”
Section: Growth Of Facility Management and Its Challenges In Turkeymentioning
confidence: 99%